HAMBATAN PEMERINTAH JEPANG DALAM IMPLEMENTASI CEDAW (CONVENTION ON THE ELIMINATION OF ALL FORMS OF DISCRIMINATION AGAINST WOMEN) TAHUN 2021-2023 - Indah, Febri Nasutra; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Japan is a developed country with the 4th economic level in the world, but in terms of gender equality Japan ranks 125th out of 146 countries in 2023. This places Japan as the country with the lowest level of gender equality in the Asia Pacific. Despite having ratified CEDAW since 1985, Japan has not been able to show significant progress in gender equality. This research analyses the barriers that make it difficult for the Japanese government to implement CEDAW. High gender gaps in political empowerment and participation opportunities in the economy are factors in Japan's low ranking. The research method used in this study is qualitative research, with a literature study data collection method through relevant writings such as journal articles, government reports, international organization reports, etc. The research was conducted using a constructivist perspective. The research was conducted using constructivism perspective and international norm implementation theory to analyze the implementation of CEDAW in Japan. The results show two factors that have hampered Japan's implementation of CEDAW, namely cultural factors and the Government of Japan. The embedded patriarchal culture makes it difficult for people to accept CEDAW. Government policies issued on CEDAW are not followed by clear mechanisms and sanctions. Resistance by culture and lack of government assertiveness caused the implementation of CEDAW to be hampered in Japan. Keywords: Implementation, Japan, CEDAW, Economy, Gender equality